Pengaruh Kompensasi dan Insentif Terhadap Kinerja Pegawai dengan Motivasi Kerja sebagai Variabel Intervening pada Dinas Perdagangan Kota Padang - Exsel Saputra; Marta Widian Sari; Vivi Nila Sari (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This study aims to find out and try to analyze the Influence of Compensation and Incentives on Employee Performance with Work Motivation as an Intervening Variable at the Padang City Trade Office. This research is a Structural Equation Modeling (SEM) model with SmartPLS 3.0 analysis tools. The population and sample of this study are employees of the Padang City Trade Office. The results of the study found that there was an influence between Compensation and Work Motivation. There is no effect between Incentives and Work Motivation. There is no effect between Compensation and employee performance. There is no effect between incentives on employee performance. There is a difference between Work Motivation and employee performance. Work Motivation mediates Compensation against employee performance. Work Motivation does not mediate incentives for employee performance at the Padang City Trade Office.